Quasar-mode Feedback in Nearby Type 1 Quasars: Ubiquitous Kiloparsec-scale Outflows and Correlations with Black Hole Properties - Rupke, David S. N.; Gültekin, Kayhan; Veilleux, Sylvain (The Astrophysical journal, 2017)
The prevalence and properties of kiloparsec-scale outflows in nearby Type 1 quasars have been the subject of little previous attention. This work presents Gemini integral field spectroscopy of 10 Type 1 radio-quiet quasars at . The excellent image quality, coupled with a new technique to remove the point-spread function using spectral information, allows the fitting of the underlying host on a spaxel-by-spaxel basis. Fits to stars, line-emitting gas, and interstellar absorption show that 100% of the sample hosts warm ionized and/or cool neutral outflows with spatially averaged velocities ( ) of 200-1300 and peak velocities (maximum ) of 500-2600 . These minor-axis outflows are powered primarily by the central active galactic nucleus, reach scales of 3-12 kpc, and often fill the field of view. Including molecular data and Type 2 quasar measurements, nearby quasars show a wide range in mass outflow rates ( to ) and momentum boosts ]. After extending the mass scale to Seyferts, dM/dt and dE/dt correlate with black hole mass ( and ). Thus, the most massive black holes in the local universe power the most massive and energetic quasar-mode winds.